Le développement des ports ultramarins : quels enjeux environnementaux ? - Rémy Louis Budoc (Développement Durable et Territoires)
The French overseas territories are very dependent on maritime transport. The interest of public authorities for outermost port regions matters should be reaffirmed to adapt these ports to new environmental challenges and foster the ecosystem in order to integrate marine and coastal concerned areas. The successful integration of port infrastructures in the sea basin of the overseas territories with a rich and unique biodiversity is therefore a major challenge for the authorities. In addition, the ecological transition to a circular economic model must be assessed by the port activities of this maritime area.